Development of a highly efficient electrochemical flow-through anode based on inner in-site enhanced TiO2-nanotubes array - Min Chen; Can Wang; Xin Zhao; Yingcai Wang; Weiqiu Zhang; Zefang Chen; Xiaoyang Meng; Jinming Luo; John Crittenden (Environment International, 2020)
This paper reports on the development of macroporous flow-through anodes. The anodes comprised an enhanced TiO2 nanotube array (ENTA) that was grown on three macroporous titanium substrates (MP-Ti) with nominal pore sizes of 10, 20, and 50 µm. The ENTA was then covered with SnO2-Sb2O3. We refer to this anode as the MP-Ti-ENTA/SnO2-Sb2O3 anode. The morphology, pore structure, and electrochemical properties of the anode were characterized. Compared with the traditional NTA layer, we found that the MP-Ti-ENTA/SnO2-Sb2O3 anode has a service lifetime that was 1.56 times larger than that of MP-Ti-NTA/SnO2-Sb2O3. We used 2-methyl-4-isothiazolin-3-one (MIT), a common biocide, as the target pollutant. We evaluated the impact of the operating parameters on energy efficiency and the oxidation rate of MIT. Furthermore, the apparent rate constants were 0.38, 1.63, and 1.24 min−1 for the 10, 20, and 50 μm nominal pore sizes of the MP-Ti substrates, respectively, demonstrating the different coating–loading mechanisms for the porous substrate. We found that hydroxyl radicals were the dominant species in the MIT oxidation in the HO· radical scavenging experiments. The radical and nonradical oxidation contributions to the MIT degradation for different current densities were quantitatively determined as 72.1%–74.8% and 25.2%–27.9%, respectively. Finally, we summarized the oxidation performance for MIT destruction for (1) the published literature on various advanced oxidation technologies, (2) the published literature on various anodes, and (3) our flow-by and -through anodes. Accordingly, we found that our flow-through anode has a much lower electrical efficiency per order value (0.58 kWh m−3) than the flow-by anodes (6.85 kWh m−3).